Cupping therapy and chronic back pain: systematic review and meta-analysis - Caroline de Castro Moura; Érika de Cássia Lopes Chaves; Ana Carolina Lima Ramos Cardoso; Denismar Alves Nogueira; Hérica Pinheiro Corrêa; Tânia Couto Machado Chianca (Universidade de São Paulo, 2018)
ABSTRACT Objectives: to evaluate the evidence from the literature regarding the effects of cupping therapy on chronic back pain in adults, the most used outcomes to evaluate this condition, the protocol used to apply the intervention and to investigate the effectiveness of cupping therapy on the intensity of chronic back pain. Method: systematic review and meta-analysis carried out by two independent researchers in national and international databases. Reference lists of systematic reviews were also explored. The quality of evidence was assessed according to the Jadad scale. Results: 611 studies were identified, of which 16 were included in the qualitative analysis and 10 in the quantitative analysis. Cupping therapy has shown positive results on chronic back pain. There is no standardization in the treatment protocol. The main assessed outcomes were pain intensity, physical incapacity, quality of life and nociceptive threshold before the mechanical stimulus. There was a significant reduction in the pain intensity score through the use of cupping therapy (p = 0.001). Conclusion: cupping therapy is a promising method for the treatment of chronic back pain in adults. There is the need to establish standardized application protocols for this intervention.